Anthocyanins-rich interventions on oxidative stress, inflammation and lipid profile in patients undergoing hemodialysis: meta-analysis and meta-regression - Martins, Isabelle C. V. S.; Maciel, Michel G.; Nascimento, José L. M. do; Mafra, Denise; Santos, Alexsandro F.; Padilha, Camila S. [UNESP] (Springer Nature, 2022)
The aim of this systematic review and meta-analysis was to evaluate the effects of anthocyanins-interventions on oxidative stress, inflammation, and lipid profile in patients undergoing hemodialysis. This systematic review and meta-analysis were registered on the International Prospective Register of Systematic Reviews (PROSPERO CRD42020209742). The primary outcome was anthocyanins-rich intervention on OS parameters and secondary outcome was anthocyanins-rich intervention on inflammation and dyslipidemia. RevMan 5.4 software was used to analyze the effect size of anthocyanins-rich intervention on OS, inflammation and dyslipidemia. Meta-analysis effect size calculations incorporated random-effects model for both outcomes 1 and 2. Eight studies were included in the systematic review (trials enrolling 715 patients; 165 men and 195 women; age range between 30 and 79 years). Anthocyanin intervention in patients undergoing hemodialysis decrease the oxidant parameters (std. mean: −2.64, 95% CI: [−3.77, −1.50], P ≤ 0.0001, I2 = 97%). Specially by reduction of malondialdehyde products in favor of anthocyanins-rich intervention (std. mean: −14.58 µmol.L, 95% CI: [−26.20, −2.96], P ≤ 0.0001, I2 = 99%) and myeloperoxidase (std. mean: −1.28 ηg.mL, 95% CI: [−2.11, −0.45], P = 0.003, I2 = 77%) against placebo group. Decrease inflammatory parameters (std. mean: −0.57, 95% CI: [−0.98, −0.16], P = 0.007, I2 = 79%), increase HDL cholesterol levels (std. mean: 0.58 mg.dL, 95% CI: [0.23, 0.94], P = 0.001, I2 = 12%) against placebo group. Anthocyanins-rich intervention seems to reduce oxidative stress, inflammatory parameters and improve lipid profile by increasing HDL cholesterol levels in patients with chronic kidney disease undergoing hemodialysis.